2003
DOI: 10.1038/ng1251
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA-producing enzyme Dicer1 is essential for zebrafish development

Abstract: MicroRNAs (miRNAs) are produced by the Dicer1 enzyme; the role of Dicer1 in vertebrate development is unknown. Here we report target-selected inactivation of the dicer1 gene in zebrafish. We observed an initial build-up of miRNA levels, produced by maternal Dicer1, in homozygous dicer1 mutants, but miRNA accumulation stopped after a few days. This resulted in developmental arrest around day 10. These results indicate that miRNA-producing Dicer1 is essential for vertebrate development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
309
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 435 publications
(321 citation statements)
references
References 10 publications
10
309
0
2
Order By: Relevance
“…Specific miRNAs control specific tissue development at a specific developmental stage (Lagos-Quintana et al, 2002). Dicer mutant in zebrafish embryos developed normal at the beginning, but embryo development arrested 8 days after fertilization (Wienholds et al, 2003). This suggests that embryo development need appropriate expression of certain miRNAs.…”
Section: Functions Of Micrornas In Animalsmentioning
confidence: 99%
“…Specific miRNAs control specific tissue development at a specific developmental stage (Lagos-Quintana et al, 2002). Dicer mutant in zebrafish embryos developed normal at the beginning, but embryo development arrested 8 days after fertilization (Wienholds et al, 2003). This suggests that embryo development need appropriate expression of certain miRNAs.…”
Section: Functions Of Micrornas In Animalsmentioning
confidence: 99%
“…14,15 Of note, Dicer-deficient mouse and zebrafish embryos are stalled at an early developmental stage, leading to developmental arrest, small size, morphological abnormalities and lethality. 16,17 Since either overexpression or underexpression of a variety of genes can promote cancer, it is not inconceivable that miRNAs may also have significant cancer-related effects. A constantly growing body of evidence indicates that miRNAs indeed play significant roles in cellular transformation and carcinogenesis, acting either as oncogenes or as tumor suppressors (reviewed in refs.…”
Section: Micrornasmentioning
confidence: 99%
“…In addition, mouse embryos hypomorphic for Dicer die mid-gestation (14). Dicer-deficient zebrafish progress much further in development, probably owing to the presence of maternally deposited Dicer transcripts (15). Depletion of maternal Dicer achieved by germ-line transplantation in zebrafish revealed that Dicer is required for morphogenesis but not cell fate specification during zebrafish embryogenesis and that the absence of miRNAs is responsible, at least in part, for this phenotype (16).…”
mentioning
confidence: 99%